Surgical reconstruction of traumatic flail chest with titanium plaques - Apaydın, Tuba (Int J Surg Case Rep, 2018)
INTRODUCTION: Multiple rib fractures exposes serious respiratory disorders and they are generally treated with non surgical methods. Nevertheless, in cases of long term pain despite medical treatment, parenchymal injury, hematoma, posture disorder and flail chest, surgery is needed. Flail chest, as the most critical form of blunt chest trauma, can disturb the hemodynamic of patient significantly and threaten life. This work has been reported in line with the SCARE criteria. PRESENTATION OF CASE: A 32 year old male patient referred to our hospital with flail chest in intubated status due to industrial accident. In physical examination, there was displaced dissociation in lower 1/3 of sternum and pericardium was palpated in the subcutaneus tissue. In thorax CT, there was fracture both in the right 7-8. costochondral and in the left 8. costochondral joints. Additionally, crepitation was palpated in these joints. There was flail chest in the right anterior hemithorax and in the lower sternum. Patient was treated with chest wall reconstruction with titanium plaques. DISCUSSION: In cases of flail chest, after a few days mechanical ventilation, implementing stabilization provides a rapid healing. CONCLUSIONS: We believe there is significant place of surgery for stabilization in proper cases.